2016
DOI: 10.1152/japplphysiol.00004.2016
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hypothermia in human sepsis is a transient, self-limiting, and nonterminal response

Abstract: Hypothermia in sepsis is generally perceived as something dysregulated and progressive although there has been no assessment on the natural course of this phenomenon in humans. This was the first study on the dynamics of hypothermia in septic patients not subjected to active rewarming, and the results were surprising. A sample of 50 subjects presenting with spontaneous hypothermia during sepsis was drawn from the 2005-2012 database of an academic hospital. Hypothermia was defined as body temperature below 36.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 49 publications
1
28
0
8
Order By: Relevance
“…Spontaneous hypothermia represents a distinct, adaptive mechanism to systemic inflammation in experimental animals [69] and in septic patients [17]. It characteristically develops in severe cases of already progressed diseases, when—instead of actively coping with the microorganism—the organism attempts to increase survival by saving its energy resources [6, 8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spontaneous hypothermia represents a distinct, adaptive mechanism to systemic inflammation in experimental animals [69] and in septic patients [17]. It characteristically develops in severe cases of already progressed diseases, when—instead of actively coping with the microorganism—the organism attempts to increase survival by saving its energy resources [6, 8].…”
Section: Discussionmentioning
confidence: 99%
“…It characteristically develops in severe cases of already progressed diseases, when—instead of actively coping with the microorganism—the organism attempts to increase survival by saving its energy resources [6, 8]. A recent study by Fonseca et al [17] revealed that spontaneous hypothermia is a transient, self-limiting, and nonterminal event in human sepsis, which underlies its biological value as an adaptive mechanism in the critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), as appears to be the case for the hypothermia that develops in humans with severe sepsis (Fonseca et al. ). This thermometabolic response is usually absent in experiments performed under anesthesia, owing to the disruption of thermoregulation by anesthetics and to the use of external heating to clamp T c at ~37°C.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, though, Fonseca et al [5] published the first effort to reconcile experimental and clinical evidence on septic hypothermia. That study revealed that, similarly to animal models of endotoxemia, hypothermia in human sepsis is usually self-limiting and transient.…”
mentioning
confidence: 99%